Rewatering Plants after a Long Water-deficit Treatment Reveals that Leaf Epidermal Cells Retain their Ability to Expand after the Leaf has Apparently Reached its Final Size - Lechner, Leandra (2008)
Background and Aims: Leaves expand during a given period of time until they reach their final size and form, which is called determinate growth. Duration of leaf expansion is stable when expressed in thermal-time and in the absence of stress, and consequently it is often proposed that it is controlled by a robust programme at the plant scale. The usual hypothesis is that growth cessation occurs when cell expansion becomes limited by an irreversible tightening of cell wall, and that leaf size is fixed once cell expansion ceases. The objective of this paper was to test whether leaf expansion could be restored by rewatering plants after a long soil water-deficit period. Methods: Four experiments were performed on two different species (Arabidopsis thaliana and Helianthus annuus) in which the area of leaves that had apparently reached their final size was measured upon reversal of water stresses of different intensities and durations. Key Results: Re-growth of leaves that had apparently reached their final size occurred in both species, and its magnitude depended only on the time elapsed from growth cessation to rewatering. Leaf area increased up to 186% in A. thaliana and up to 88% in H. annuus after rewatering, with respect to the leaves of plants that remained under water deficit. Re-growth was accounted for by cell expansion. Increase in leaf area represented actual growth and not only a reversible change due to increased turgor. Conclusions: After the leaf has ceased to grow, leaf cells retain their ability to expand for several days before leaf size becomes fixed. A response window was identified in both species, during which the extent of leaf area recovery decreased with time after the ‘initial’ leaf growth cessation. These results suggest that re-growth after rewatering of leaves having apparently attained their final size could be a generalized phenomenon, at least in dicotyledonous plants.